The Right Ventricle under Pressure: Evaluating the Adaptive and Maladaptive Changes in the Right Ventricle in Pulmonary Arterial Hypertension using Echocardiography (2013 Grover Conference Series). (1st March 2015) - Harrison, Alexis; Hatton, Nathan; Ryan, John J.
Abstract : The importance of the right ventricle (RV) in pulmonary arterial hypertension (PAH) has been gaining increased recognition. This has included a reconceptualization of the RV as part of an RV–pulmonary circulation interrelated unit and the observation that RV function is a major determinant of prognosis in PAH. Noninvasive imaging of RV size and function is critical to the longitudinal management of patients with PAH, and continued understanding of the pathophysiology of pulmonary vascular disease relies on the response of the RV to pulmonary vascular remodeling. Echocardiography, in particular the newer echocardiographic measurements and techniques, allows easy, readily accessible means to assess and follow RV size and function.